2022
DOI: 10.3390/tomography8050178
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced MRI in the Abdomen of Mice with High Temporal and Spatial Resolution Using Stack-of-Stars Sampling and KWIC Reconstruction

Abstract: Application of quantitative dynamic contrast-enhanced (DCE) MRI in mouse models of abdominal cancer is challenging due to the effects of RF inhomogeneity, image corruption from rapid respiratory motion and the need for high spatial and temporal resolutions. Here we demonstrate a DCE protocol optimized for such applications. The method consists of three acquisitions: (1) actual flip-angle B1 mapping, (2) variable flip-angle T1 mapping and (3) acquisition of the DCE series using a motion-robust radial strategy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…These challenges include increasing SNR, reducing motion artifacts, optimizing protocols for improving repeatability and reproducibility, and improving sensitivity and specificity. Several manuscripts in this special issue contributed by the CIRP teams present the progress on the development of new technology and methodology [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Advanced and Emerging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges include increasing SNR, reducing motion artifacts, optimizing protocols for improving repeatability and reproducibility, and improving sensitivity and specificity. Several manuscripts in this special issue contributed by the CIRP teams present the progress on the development of new technology and methodology [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Advanced and Emerging Methodsmentioning
confidence: 99%
“…MR imaging of PDAC in GEMMs suffers from respiratory motion and increased magnetic susceptibility artifacts at high magnetic fields. Using the radial k -space sampling technique, Pickup et al demonstrated that respiration artifact-free images with good SNR are obtained for orthotopic PADC in GEMMs, leading to robust estimation of quantitative metrics from DCE MRI [ 34 ]. Dynamic hyperpolarized 13 C metabolic imaging can provide a quantitative assessment of the pyruvate to lactate conversion rate, k pl , as a biomarker for cancer aggressiveness and therapeutic response.…”
Section: Advanced and Emerging Methodsmentioning
confidence: 99%
“…Quantitative imaging biomarkers (QIB) including tumor size, apparent diffusion coefficient (ADC), K trans , V e , and T 1 relaxation time of the tumor are obtained for the co-clinical trial. We developed motion-resistant radial k-space sampling acquisition and image reconstruction protocols [55,56]. Further optimization of these protocols has led to respiratory motion-free DW and DCE images acquired from free-breathing mice without the need for respiration gating [56,57]; a deep-learning method to accelerate the DW-MRI acquisition is being developed.…”
Section: Penn Quantitative Mri Resource For Pancreatic Cancermentioning
confidence: 99%
“…We developed motion-resistant radial k-space sampling acquisition and image reconstruction protocols [55,56]. Further optimization of these protocols has led to respiratory motion-free DW and DCE images acquired from free-breathing mice without the need for respiration gating [56,57]; a deep-learning method to accelerate the DW-MRI acquisition is being developed. Tumor ADC and K trans maps are shown in Figure 6 and capture the spatial heterogeneities of these features.…”
Section: Penn Quantitative Mri Resource For Pancreatic Cancermentioning
confidence: 99%